Comment on 'Adiabatic shear instability is not necessary for adhesion in cold spray'. (15th March 2019) - Assadi, H.; Gärtner, F.; Klassen, T.; Kreye, H.
Abstract: This paper concerns the statements of a recently published article on the mechanism of particle bonding (adhesion) in cold spraying of metallic materials, by Hassani-Gangaraj et al., Acta Materialia 158 (2018). The core statements of the above article are that (1) jetting is the cause of particle bonding, as the title implies, (2) adiabatic shear instability is not necessary for jet formation, and (3) jetting and particle bonding are governed by the bulk speed of sound. In this paper we argue that the first statement is inaccurate, the second is correct but not new, and the third is incorrect.